Assistance for Toddler Mothers and Health Cadres in Utilizing Boardgames as an Alternative to Gadgets for Toddlers to Support Children's Growth and Development - Nurlailis Saadah; Nani Surtinah; Rahayu Sumaningsih; Budi Yulianto (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
In Magetan the number of gadget use and gadget dependence on children is relatively high. The results of a 2019 study showed that most children play gadgets for 5-10 minutes without their parents' assistance. A small number of children play traditional games, watch TV and play at home. The results of the preliminary interviews show that the majority of children are not familiar with board games, some do but have never played them. Some parents never buy toys for their children because according to them, children play enough at school. On the other hand, stimulating the growth and development of children is the responsibility of the community so that parents must be involved and participate and be active in its implementation. Data from the Magetan Health Office shows that part of the stimulation of development has been carried out by mothers for their children. From the results of the interviews it was found that 54.5% of mothers stimulated by inviting them to sing, ride bicycles, but not regularly every day, when they are free while watching TV. Some other mothers never do stimulation because they don't know how to do it so that their children develop as they are. To increase community participation, the solutions offered are counseling, outreach, training for mothers of toddlers, and health cadres. This activity collaborated with village midwives, health centers and facilitators from universities. The main objective of the activity is to use the media to play board games in order to reduce gadget dependence on children. The fundamental contribution of this activity is increasing the application of science and technology in the community, increasing understanding and skills of the community. The community can realize that there are health problems that must be handled independently as early as possible.